HS-GC-IMS detection of volatile organic compounds in cistanche powders under different treatment methods. (1st August 2022) - Zhou, Shi-qi; Feng, Duo; Zhou, Ya-xi; Zhao, Jian; Zhao, Jiang-yan; Guo, Yu; Yan, Wen-jie
Abstract: Cistanche is a valuable Chinese medicinal material with medicinal and edible value. In order to study the effects of different treatment methods on the volatile components in cistanche. First, the current study carried out the synergistic, ultra-fine powdering, alcohol extraction and water extraction treatment of cistanche, and then used the HS-GC-IMS method to detect the volatile components, and established the characteristic fingerprints of the synergistic cistanche powder (a), fresh cistanche powder (b), ultra-micro meat cistanche powder (c), the water extract of cistanches powder (d) and the ethanol extract of cistanches (e). A total of 48peaks were detected, and 32 volatile compounds were identified, including 17 aldehydes, 5 ketones, 1 furan, 5 alcohols, phenols, 1 lactone, 3 ester compounds. In addition, the similarity analysis of PCA and fingerprinting showed that the volatile components of the five treatment methods could be significantly distinguished. The results showed that the types and contents of volatile components in synergistic cistanche were relatively low, the volatile components and types in fresh cistanche were relatively high, and the five treatment methods each had their own characteristic volatile components. Highlights: Analysis of volatile constituents of cistanche in five different treatments. Different treatments affect the volatile substances characteristic of cistanche. Identified a total of 48 peaks of cistanche and 32 compounds. Synergistic treatment will increase the volatilization of cistanche flavor substances. Contributes to cistanche quality analysis and product development.